2019
DOI: 10.1111/aji.13184
|View full text |Cite
|
Sign up to set email alerts
|

Gasdermin D: Evidence of pyroptosis in spontaneous preterm labor with sterile intra‐amniotic inflammation or intra‐amniotic infection

Abstract: Problem: Pyroptosis, inflammatory programmed cell death, is initiated through the inflammasome and relies on the pore-forming actions of the effector molecule gasdermin D. Herein, we investigated whether gasdermin D is detectable in women with spontaneous preterm labor and sterile intra-amniotic inflammation or intra-amniotic infection. Method of study: Amniotic fluid samples (n = 124) from women with spontaneous preterm labor were subdivided into the following groups: (a) those who delivered at term (n = 32);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 176 publications
1
31
0
Order By: Relevance
“…The increased concentrations of active caspase-4 suggest that noncanonical inflammasome activation may occur in the context of preterm labor resulting from intra-amniotic infection due to Gram-negative bacteria. Recently, we also found that amniotic fluid concentrations of the adaptor protein ASC (252) and the effector molecule of pyroptosis GSDMD (253) were increased in women with preterm labor and intra-amniotic infection compared with those without this clinical condition. Both ASC and GSDMD are also overexpressed by the chorioamniotic membranes of women with preterm labor and intra-amniotic infection.…”
Section: Inflammasomes In Preterm Labor and Birthmentioning
confidence: 86%
“…The increased concentrations of active caspase-4 suggest that noncanonical inflammasome activation may occur in the context of preterm labor resulting from intra-amniotic infection due to Gram-negative bacteria. Recently, we also found that amniotic fluid concentrations of the adaptor protein ASC (252) and the effector molecule of pyroptosis GSDMD (253) were increased in women with preterm labor and intra-amniotic infection compared with those without this clinical condition. Both ASC and GSDMD are also overexpressed by the chorioamniotic membranes of women with preterm labor and intra-amniotic infection.…”
Section: Inflammasomes In Preterm Labor and Birthmentioning
confidence: 86%
“…In particular, we review how inflammation is propagated in different tissue compartments at the maternal-fetal interface, the role of resident cells interacting with immune cells at the interface, the role of inflammatory mediators, and how host-microbe interactions affect pathology. Although sterile inflammation (3,4), environmental pollutants (5)(6)(7), cigarette smoke (8,9), and other toxicants play an important role in the pathogenesis of IUI, these considerations are beyond the scope of this review.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of inflammasomes also induces gasdermin D cleavage, leading to the formation of membrane pores by the N-terminal fragment, also called the pyroptotic fragment (96). Recently, Gomez-Lopez et al (41,73) associated gasdermin D expression and subsequent pyroptosis with both term and preterm deliveries. In the present study, the precursor and pyroptotic forms of gasdermin D were more strongly expressed in AECs following FSL-1 treatment than in the untreated condition.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is involved in both the normal physiological and the pathological rupture of human fetal membranes during parturition. Recently, particular attention has been paid to inflammasomes and their molecular actors, as these have been linked to preterm prelabor rupture of membranes (pPROM) ( 68 , 69 ), chorioamnionitis ( 42 , 46 , 70 ), preterm labor ( 71 73 ), and preeclampsia ( 48 , 50 , 74 ). Thus, a better characterization of inflammasome-related inflammation seems to be essential in order to prevent potentially adverse pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 99%